Role of Serum Albumin-and Bilirubin Biomarkers in Glaucoma Patients - Rubia Ahmad, Maria Sarfaraz, Muhammad Faisal Javaid, Alia Sarfaraz, Ahsan Farooq, Muhammad Nazir Awan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compared the levels of serum albumin (ALB) and bilirubin (BIL) in glaucoma patients to those of a control group of individuals who did not have the glaucoma. Methods: A total of 50 glaucoma patients and 50 healthy controls were recruited from January-2022 to April-2022. Diagnosis of glaucoma was based on ophthalmology department. We recruited only those patients who were not having any kind of infection or were not taking antibiotics at the time of sample withdrawal. Serum ALB and BIL levels were measured in all patients. Results: Mean age was 59.1±7.6 years in Glaucoma and 61.3±6.5 years in controls (p-value 0.12). There were 28 (56.0%) male patients in glaucoma and 27 (54%) male patients in controls (p-value 0.84). Mean serum albumin (ALB) levels were lower in glaucoma patients; 42.5±0.67 g/L versus 45.2±0.81 g/L in healthy controls (p-value <0.0001). Serum bilirubin levels were also lower in glaucoma patients; 15.1±1.80 mmol/L versus 18.3±1.95 mmol/L in healthy controls (p-value <0.0001). Conclusion: Serum ALB and BIL are lower in glaucoma patients. However, ideal cut off values of these parameters are still to be decided to predict glaucoma.